PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE AFTER EFFECT PADA MATERI IN THE KITCHEN KELAS V DI UPT SDN 060866 KEC. MEDAN TIMUR - Martha Traci Br Simanjuntak; Tiarnita M.S Br Siregar; Eva Betty Simanjuntak; Lidia Simanihuruk; Dody F. Pandimun Ambarita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This research was motivated by the monotonous English learning process for the "In The Kitchen" topic in fifth grade, where teachers relied only on textbooks so that students tended to be passive and had difficulty remembering vocabulary. This study aimed to develop, and to determine the feasibility, practicality, and effectiveness of an animated video learning medium based on Adobe After Effect. This research and development (R&D) study used the Borg and Gall model, simplified into six stages, involving 25 fifth-grade students of UPT SDN 060866, Kecamatan Medan Timur, as the trial subjects. Data were collected through material and media expert validation questionnaires, teacher and student response questionnaires, and pretest-posttest results, then analyzed descriptively and with the N-Gain Score formula. The results showed that the developed media obtained a material validation score of 93.33%, a media validation score of 82.66%, and a test validation score of 95%, all categorized as highly feasible. The practicality results reached 95% based on teacher responses and 95.6% based on student responses, both categorized as highly practical. The effectiveness test produced an N-Gain score of 0.71, categorized as high. It can be concluded that the Adobe After Effect-based animated video learning medium on the "In The Kitchen" topic is highly feasible, highly practical, and effective for improving the English learning outcomes of fifth-grade elementary school students.